2004
DOI: 10.1111/j.0023-9216.2004.03801003.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Assumption that Adult Businesses Are Associated with Crime in Surrounding Areas: A Secondary Effects Study in Charlotte, North Carolina

Abstract: Recent Supreme Court decisions have signaled the need for sound empirical studies of the secondary effects of adult businesses on the surrounding areas for use in conjunction with local zoning restrictions. This study seeks to determine whether a relationship exists between adult erotic dance clubs and negative secondary effects in the form of increased numbers of crimes reported in the areas surrounding the adult businesses, in Charlotte, North Carolina. For each of 20 businesses, a control site (matched on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 18 publications
0
47
0
Order By: Relevance
“…There has been some community mobilization against massage parlors, strip clubs, and adult video stores -either because of what they symbolize (immorality, degradation of women) or because of some alleged negative effects on the surrounding area. A sophisticated study by Linz (2004) found that crime was much more prevalent in the immediate vicinity of bars and gas stations than in the area surrounding strip clubs, partly because of the security measures taken by strip clubs.…”
Section: Notesmentioning
confidence: 99%
“…There has been some community mobilization against massage parlors, strip clubs, and adult video stores -either because of what they symbolize (immorality, degradation of women) or because of some alleged negative effects on the surrounding area. A sophisticated study by Linz (2004) found that crime was much more prevalent in the immediate vicinity of bars and gas stations than in the area surrounding strip clubs, partly because of the security measures taken by strip clubs.…”
Section: Notesmentioning
confidence: 99%
“…The extent to which commercial sex should be treated as potentially 'harmful' is hindered by the paucity of evidence about the nature and extent of its impacts. For example, currently, there is a reliance on a small number of US studies on 'secondary effects' that draw markedly different conclusions about the impacts of sex businesses in different cities (e.g., Linz et al, 2004). Regardless of whether decisions regarding harm are based on evidence or perception, the idea that LGBTI sexual commerce is more deviant than heterosexual sexual commerce has meant that LGBTI sex commerce has traditionally been subject to moral campaigns of prohibition, or subject to being socially and spatially marginalized.…”
Section: The Regulation Of Lgbti Commercial Sexmentioning
confidence: 99%
“…Recent scholarship has explored neighborhood spatial variation in crime across several U.S. cities (e.g., Austin, Charlotte, Chicago, Cincinnati, Cleveland, Columbus, New York City, St. Louis, San Diego, and Seattle) and has considered a wide variety of attributes. Among the factors considered in recent work are the prevalence of adult "business establishments" (Linz et al 2004), the presence of illicit drug markets (Martinez, Rosenfeld, and Mares 2008) and licensed alcohol outlets (Roncek 1981;Peterson, Krivo, and Harris 2000;Pridemore and Grubesic 2011), legal cynicism (Kirk and Papachristos 2011), physical and social disorder (Sampson and Raudenbush 1999;Taylor 2001), order maintenance policing (Rosenfeld, Fornango, and Rengifo 2007), social ties, collective efficacy, and institutional strength (Sampson, Raudenbush, and Earls 1997;Bellair 2000;Triplett, Gainey, and Sun 2003), gentrification , the density of commerce (Browning et al 2010), and the implication of the "built environment" more generally (Matthews, et al 2010). The diversity of concentration in recent neighborhood crime research has been balanced, however, by steady attention to a common set of demographic predictors of the spatial distribution of crime.…”
Section: "Global" Contemporary Neighborhood Models Of Crimementioning
confidence: 99%